Understanding the seed ecology of southwest Australian Rutaceae to improve restoration in a biodiversity hotspot - Just, Michael (Curtin University, 2022)
In southwest Australia there is a significant need to restore vegetation communities impacted by anthropogenic activities. The series of experiments undertaken over the course of this thesis focus on a notoriously difficult-to-germinate plant family, the Rutaceae. Through the application of field- and lab-based experiments, avenues for seed-based propagation of southwest Australian Rutaceae have been developed, allowing for more effective restoration approaches based upon an improved understanding of seed ecology.